THE INFLUENCE OF PRICE, PROMOTION, AND SERVICE QUALITY ON BUYING INTEREST IN ONLINE CLOTHING ON THE SHOPEE PLATFORM (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
In the digital era that continues to develop, the phenomenon of online sales has become the center of attention in the realm of e-commerce. One of the main platforms that stands out is Shopee, which has become a favorite destination for millions of consumers looking for a variety of products at competitive prices. In this look, researcher will explore changing trends in online selling, especially in the context of Shopee, as well as how this phenomenon affects consumer behavior and the development of e-commerce as a whole. This research aimed to determine: 1) The effect of price simultaneously on buying interest, 2) the effect of simultaneous promotion on buying interest, 3) the simultaneous influence of service quality on buying interest. The sampling technique used a purposive sampling method of 100 respondents who meet the criteria. The data analysis techniques in this research are descriptive analysis, classical assumption testing, and multiple linear regression analysis using the SPSS application program. The research results showed that price, promotion and service quality simultaneously influence purchasing interest. This journal contributes to a deeper understanding of e-commerce dynamics and provides recommendations to help business professionals develop and implement effective strategies to increase consumer purchasing intentions.
Keywords: Price; Promotion; Service quality; Purchase interest